Europium (III) chelate microparticle-based lateral flow immunoassay strips for rapid and quantitative detection of antibody to hepatitis B core antigen. Issue 1 (December 2017) - Liang, Rong-Liang; Deng, Qiao-Ting; Chen, Zhen-Hua; Xu, Xu-Ping; Zhou, Jian-Wei; Liang, Jun-Yu; Dong, Zhi-Ning; Liu, Tian-Cai; Wu, Ying-Song
Abstract Quantitative hepatitis B core antigen (anti-HBc) measurements could play an important role in evaluating therapeutic outcomes and optimizing the antiviral therapy of chronic hepatitis B infection. In this study, we have developed a simple and rapid fluorescence point-of-care test based on a lateral flow immunoassay (LFIA) method integrated with Eu (III) chelate microparticles to quantitatively determine anti-HBc concentrations in serum. This assay is based on a direct competitive immunoassay performed on lateral flow test strips with an assay time of 15 min. The Eu (III) chelate microparticle-based LFIA assay could quantitatively detect anti-HBc levels with a limit of detection of 0.31 IU mL−1, and exhibited a wide linear range (0.63–640 IU mL−1 ). The intra- and inter-assay coefficients of variation for anti-HBc were both less than 10% and a satisfactory dilution test and accuracy were demonstrated. There were no statistically significant differences in sensitivity or specificity in serum samples between the Eu (III) chelate microparticle-based LFIA strips and the Abbott Architect kit. A simple, rapid and effective quantitative detection of anti-HBc was possible using the Eu (III) chelate microparticle-based LFIA strips. The strips will provide diagnostic value for clinical application.